Alteration of gene expression in human cumulus cells as a potential indicator of oocyte aneuploidy. - Fragouli, E; Wells, D; Iager, A; Kayisli, U; Patrizio, P (2012)
BACKGROUND: Human female meiosis is particularly error prone, leading to the generation of aneuploidy, a problem which increases dramatically with advancing age. Despite being of great clinical importance, the genesis of oocyte aneuploidy remains poorly understood. Cumulus cells (CCs) surround oocytes in antral follicles and play a crucial role in regulating their maturation. During this investigation, we aimed to obtain an insight into the follicular environment of oocytes that become aneuploid and identify non-invasive markers of oocyte chromosome status and competence. METHODS: Microarray comparative genomic hybridization was used to assess oocyte ploidy. Expression of 96 genes was examined via a large real-time PCR experiment in 51 CC samples, whereas an additional 26 CC clumps were used for a more focused real-time PCR experiment assessing just three genes. Gene selection was based on the results of a previous microarray analysis comparing the transcriptome of CCs from normal and aneuploid oocytes. RESULTS: Fifty eight of the investigated genes were confirmed to be expressed in CCs. Patterns of expression were generally similar among all CC samples, regardless of the chromosomal status of the corresponding oocyte. However, two genes, SPSB2 and TP53I3, were both significantly down-regulated in CCs from chromosomally abnormal oocytes (P<0.05). The expression of SPSB2 was also found to display a strong trend towards up-regulation in the CCs of oocytes that produced a healthy live birth (P=0.054). CONCLUSIONS: In the current study, SPSB2 and TP53I3 exhibited highly significant differences in their expression between CCs of normal and chromosomally abnormal oocytes. SPSB2 is involved in intracellular signalling and homeostasis, whereas TP53I3 regulates carbohydrate metabolism and apoptosis. We speculate that both these genes might have the potential to serve as non-invasive markers of oocyte aneuploidy.